Antioxidant, cytotoxic, and genotoxic potentials of the gum of Ferula gummosa Boiss on PC-3 cells - Fatemeh Eizadifard; Majid Tafrihi; Maryam Mohadjerani (Mashhad University of Medical Sciences, 2023)
Objective: Ferula gummosa Boiss is a well-known Iranian endemic plant that has been used in Iranian traditional medicine against various diseases. This study aimed to evaluate the antioxidant and cytotoxic capacity of F. gummosa gum on prostate cancer PC-3 cells.Materials and Methods: In this study, we evaluated the total phenolic and flavonoid contents, and antioxidant potentials of the gum. The MTT experiment was conducted to assess the cytotoxic potential of the gum on PC-3 cells. The clonogenic, micronucleus formation, and acridine orange/ethidium bromide staining methods were used to evaluate the survival and proliferation of PC-3 cells. DNA degradation and caspase 3/7 activity evaluations were used to assess apoptosis. The inhibitory effect on the migration of PC-3 cells was examined by in vitro wound-healing experiment.Results: Total phenolic and flavonoid contents, and antioxidant potential of the gum were 9.22 mg of gallic acid equivalent (GAE)/g, 3.6 mg of quercetin equivalents (QE) /g of the extract, and 13 μg/ml, respectively (compared to gallic acid and quercetin, respectively) (p<0.05). The IC50 value was 9.14 µg/ml for 48 hours (compared to non-treated cells) (p<0.01).  The pattern of DNA degradation, and caspase 3/7 activity levels (compared to non-treated cells) (p<0.05) proposed decreased cell viability that may be due to apoptosis induction. Microscopic observations revealed nuclear condensation, a significant increase in the formation of micronuclei, and inhibition of forming colonies (compared to non-treated cells) (p<0.01) in PC-3 cells treated with 8 and 10 μg/ml of the gum. Wound-healing assessment showed the migration suppression potentials of the gum (compared to non-treated cells) (p<0.05).Conclusion: These results indicate that F. gummosa has considerable antioxidant and cytotoxic properties that can make it a good nominee for subsequent investigations.